2010
DOI: 10.1007/s00220-010-1078-8
|View full text |Cite|
|
Sign up to set email alerts
|

Fluctuations of the Nodal Length of Random Spherical Harmonics

Abstract: Using the multiplicities of the Laplace eigenspace on the sphere (the space of spherical harmonics) we endow the space with Gaussian probability measure. This induces a notion of random Gaussian spherical harmonics of degree n having Laplace eigenvalue E = n(n + 1). We study the length distribution of the nodal lines of random spherical harmonics.It is known that the expected length is of order n. It is natural to conjecture that the variance should be of order n, due to the natural scaling. Our principal resu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
167
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 101 publications
(176 citation statements)
references
References 21 publications
9
167
0
Order By: Relevance
“…Nn ; this situation (customarily called arithmetic Berry's cancellation, see [KKW]) is similar to the cancellation phenomenon observed by Berry in a different setting, see [Be,W1].…”
Section: Ensupporting
confidence: 71%
“…Nn ; this situation (customarily called arithmetic Berry's cancellation, see [KKW]) is similar to the cancellation phenomenon observed by Berry in a different setting, see [Be,W1].…”
Section: Ensupporting
confidence: 71%
“…To be clear, as given in Marinucci et al (2017), as → ∞, and, setting L: = + 1 2 , we have that More explicitly, it was shown in Marinucci and Wigman (2014) that, as → ∞, to find a better approximation, we evaluate numerically the constant see the Appendix for some analytic results. Hence, we conclude that, up to smaller order terms, Then, the variance of the scaled sample trispectrum M is asymptotically given by Finally, let us recall that these results, as in Marinucci et al (2017), Rossi (2015), Todino (2018b) and Wigman (2010), refer to the boundary length, not to the first Lipschitz-Killing curvature; there is hence a difference of a factor 2 in the expected value, and a factor 4 in the variance. The values in the Table 2 refer to the Lipschitz-Killing curvature; hence, they have been normalized accordingly.…”
Section: (Half) the Boundary Length (K = 1)mentioning
confidence: 57%
“…For u = 0, the leading term in the previous expression disappears (the so‐called Berry's cancellation phenomenon, see Berry (), Wigman ()) and the variance is of smaller order; more precisely, we have that (Wigman, )VarscriptL1false(Au(f;double-struckS2)false)=log128+Ofalse(1false);(the same happens for shrinking subdomains of the sphere, see Todino ()). It is important to notice that the difference between the leading and remainder terms is here only of logarithmic order, and we hence expect a less precise approximation (in relative terms) in the simulations.…”
Section: Characterization Of Excursion Sets For Random Spherical Harmmentioning
confidence: 93%
See 1 more Smart Citation
“…Note that the mean (5.36) has the same form as in the toral or spherical case (see Remark 2.3), and the asymptotic variance (5.37) is of lower order than expectedas predicted by Berry in [Ber02]. Thanks to the symmetry of nodal lines on the two dimensional sphere [Wig10, §1.6.2], the result on the asymptotic variance for the nodal length on S 2 (2.13) obtained by Wigman in [Wig10] is of course consistent to Berry's prediction ((5.37) or [Ber02]).…”
Section: Nodal Lengths: Recent Resultsmentioning
confidence: 74%